Reaching for the dream: A narrative study of skilled women domestic workers - Astagini, Nuria; Sarwono, Billy K. (Jurnal Studi Komunikasi, 2022)
Women domestic workers are often associated with females whose only task is completing domestic work. However, this construction has changed along with the development of the labour industry. Currently, they are associated with skilled domestic workers. The relationship between women domestic workers and their employer that was previously based on kinship is supposed to have shifted to a formal relationship, with work and wage agreements. This construction is also strengthened by the presence of social media, as a means for conveying their narrative as skilled workers and not just servants for their employers. This study examines the process of symbolic interactionism in women domestic workers through their narratives as skilled domestic workers. The data was collected qualitatively from four women domestic workers in the Jakarta area as the research participants. As a metropolitan city, Jakarta has the highest number of domestic workers in Indonesia. Based on the data analysis, women domestic workers conceptualised their profession as experienced and versatile individuals in performing various domestic work and are the backbone of their respective families. Therefore, this conceptualisation shows that the participants can break away from the stereotype that domestic workers are lowly and unskilled workers. The interaction between participants and their employer raises non-physical symbols reflecting dedication and loyalty. In addition, the interaction process is a learning tool for subjects to obtain resources that equalise them with other workers in the domestic sector.